تطبيق وسيلة FUZZLE في تدريس مهارة الكلام بـ SMP IT AL FARABI BILINGUAL SCHOOL ACEH BESAR - Halimahtul Saqdiah Hasibuan; Muslim, Buhori; Ridha, Muhammad; Ninoersy, Tarmizi (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2025)
The background of this study is based on the importance of mastering speaking skills as one of the key competencies in language learning, especially Arabic. This study aims to examine the impact of puzzle media on Arabic speaking skills at SMP IT Al Farabi Bilingual School in Aceh Besar. The research methodology used is an experiment with a pre-test and post-test control group design. The research sample consisted of two groups of eighth-grade students: the experimental group using puzzle media and the control group using traditional media. The data collection technique used in this study was an oral test, which was assessed based on aspects of fluency, vocabulary, language structure, and speaking proficiency. The data collected in the study were then analyzed using descriptive statistics by comparing the mean scores and inferential statistics using the t-test. The results of the study showed that puzzle media had a significant impact on students' Arabic speaking skills. This is evident in the higher mean score of the experimental group (90.02 with a very high score) compared to the control group (50.31 with a low score). Furthermore, the independent, paired t-test showed that the significance value was less than 0.05, indicating a difference in Arabic speaking ability between students who used puzzle media and those who did not. Therefore, puzzle media can be used as an alternative means of improving students' Arabic language skills.